DIFFERENCES IN STRESS, SELF-ESTEEM BETWEEN SMOKING AND NON-SMOKING ACEHNESE ADOLESCENTS - Amalia, Dina -; Khan, Shams U Rehman; Sim, Chee Chew (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2016)
There is an increasing number of young smokers in Indonesia that has become a serious concern in recent years. Therefore, this study aimed to examine Indonesian adolescents’ smoking based on related variables i.e. stress and self-esteem. Purposive random sampling was used in this study with a set inclusion criteria including male at age of 15 to 18 years old. A total of 106 students (54 smokers and 52 non smokers) from four senior high schools in Banda Aceh, Indonesian participated. The measures used were the Perceived Stress Scale (PSS), and Rosenberg Self-Esteem Scale (RSES).The result of this study founded that there were differences in stress and self-esteem level as well as certain parenting practices between smoking and non-smoking adolescents.